Discourses of Labour Protest in Post-Communist Lithuania - Woolfson, Charles (Respectus Philologicus, 2005)
This article explores the emergent discourses of labour protests that have accompanied the transition from communism to the market economy. Building on the ground-breaking theoretical paradigm of V. N. Voloshinov and contemporary attempts by Marxist scholars to develop materialist socio-linguistics, the gradual emergence of class-based labour discourses in the new market economies of Central and Eastern Europe is examined. A number of recent labour protests in ex-Soviet Lithuania are examined. The complex articulation of labour identities is charted. Their legitimisation as social actors with “independent” demands in the context of transitional Lithuanian society is analysed through protest discourses. Discourses of labour protest have emerged in contestation and tension with seemingly contradictory attempts to impose a “supra class” ideology. The imposition of both neo-liberal ideology, which seeks to exclude organised labour from an independent role in civil society, and at the same time, the cultivation of the language of social partnership, which seeks to incorporate labour in national tripartite structures, are complementary attempts to forestall the emergence of more radical class-based discourses. The emergence of dialogic discourses between labour and capital and the forms of their social resonance reveals much about the current limits of labour protest in the new market economies. Such discourses also reveal many possible future forms of labour contestation as the new market economies of Central and Eastern Europe are incorporated into the newly enlarged European Union.
Keywords: Discourse; Voloshinov; labour protest; post-communism; Lithuania; European Enlargement